Chibi. Shang bu ji xia bu = Red cliff. Part 1 and 2 [videorecording (DVD)] Part I & part II - Woo, John, 1948-; Woo, John, 1948-; Woo, John, 1948-; Leung, Tony Chiu Wai, 1962-; Liang, Jiahui; Kaneshiro, Takeshi; Zhang, Fengyi (6-shooter film series., 2010)
"[T]he epic historical drama based on a legendary 208 A.D. battle that heralded the end of the Han Dynasty. A power-hungry Prime Minister-turned-General Cao Cao seeks permission from the Han Dynasty Emperor to organize a southward-bound mission designed to crush the two troublesome warlords who stand in his way, Liu Bei and Sun Quan. Vastly outnumbered by Cao Cao's brutal, fast-approaching army, the warlords band together to mount a heroic campaign-unrivaled in history-that changes the face of China forever"--Container.